Current Trends in Mathematical Analysis and Its Interdisciplinary Applications 2019
DOI: 10.1007/978-3-030-15242-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Spacetimes as Topological Spaces, and the Need to Take Methods of General Topology More Seriously

Abstract: Why is the manifold topology in a spacetime taken for granted? Why do we prefer to use Riemann open balls as basic-open sets, while there also exists a Lorentz metric? Which topology is a best candidate for a spacetime; a topology sufficient for the description of spacetime singularities or a topology which incorporates the causal structure? Or both? Is it more preferable to consider a topology with as many physical properties as possible, whose description might be complicated and counterintuitive, or a topol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…They sought answers to "Why is the manifold topology in a spacetime taken for granted? "Why do we prefer to use Riemann open balls as basic-open sets, while there also exists a Lorentz metric [41]" shaped questions. In short, we should consider new topologies for the space-time…”
Section: Discussionmentioning
confidence: 99%
“…They sought answers to "Why is the manifold topology in a spacetime taken for granted? "Why do we prefer to use Riemann open balls as basic-open sets, while there also exists a Lorentz metric [41]" shaped questions. In short, we should consider new topologies for the space-time…”
Section: Discussionmentioning
confidence: 99%
“…Consider the chronological order ≪, on a relativistic spacetime manifold M. Then, ≪ in ∩ B h ǫ (x). Low (see [5]) has shown that the Limit Curve Theorem fails to hold for the Path topology, and so the formation of a basic contradiction present in the proofs of all singularity theorems, fails as well (for a more extensive discussion see [11], [9] and [16]).…”
Section: Curved Spacetimesmentioning
confidence: 99%
“…For a critical survey on this discussion, we refer to[14].1 Natural vs. Artificial Topologies on a Relativistic Spacetime…”
mentioning
confidence: 99%